Emerging technologies for biological recording. (20th April 2015) - August, Tom; Harvey, Martin; Lightfoot, Paula; Kilbey, David; Papadopoulos, Timos; Jepson, Paul
<x xml:space="preserve">Abstract</x> Technology has played an important role in biological recording for hundreds of years, from the invention of the microscope to the microprocessor. We review current and emerging technologies that are changing the way we study and record the natural world. From websites to smartphones, data capture is becoming easier, faster and more accessible. Increases in data volume and wider participation raises concerns over data quality, which are being addressed with accurate sensors, automated validation tools, and verification platforms that utilize expert taxonomists and collective intelligence to ensure the highest level of quality possible. Data curation and interoperability have been transformed in the information age. The need to collate data at continental and global scales and across institutions continues to drive the formation of standardized data formats and taxonomies. Once collated these data can be analysed using high‐performance computing, and used to provide valuable feedback in the form of interactive visualizations, computer‐generated text or even game‐like rewards. We also address issues arising from these technological developments. For example: how will the role of the expert naturalist change? Is biological recording undergoing a revolutionary or evolutionary process? How is technology leading to the empowerment of the public? © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.